Rethinking Islamic Philanthropy in Pakistan: A Conceptual Exploration of Faith-Based Giving and Social Change - Kaleemullah Dawood; Siti Rohmah; Salsabiila Fidra Ramadhania; Fadila Rahmadani (MD Research Center Yogyakarta, 2026)
This study aims to develop a comprehensive conceptual framework for understanding Islamic philanthropy in Pakistan as a complex social system capable of driving structural change beyond the dominant charitable paradigm. Despite the significant growth of Islamic philanthropic instruments such as zakat, sadaqah, and waqf in Pakistan, existing practices remain predominantly oriented toward short-term relief rather than sustainable empowerment, while scholarly literature has largely treated theological, institutional, and managerial dimensions in isolation. Employing a traditional literature review method, this study examines a wide range of academic books, journal articles, and institutional reports to identify patterns and tensions within Pakistan's philanthropic landscape. The findings reveal that Islamic philanthropy operates as a dynamic field shaped by interactions among state actors, religious institutions, civil society, and market entities, where governance structures and social capital determine whether resources contribute to systemic transformation or merely reproduce existing inequalities. This study concludes that repositioning Islamic philanthropy as a transformative social system requires an integrated approach combining regulatory reform, institutional innovation, and cultural reorientation, with significant implications for policymakers and development practitioners seeking to align Islamic social finance with sustainable development goals in Pakistan.